Perbedaan Metode Pembelajaran Aktif Tipe Quiz Team Dengan Metode Konvensional Plus Terhadap Hasil Belajar Ilmu Konstruksi Bangunan - Puti Lenggo Geni; Amos Neolaka (LPPM Universitas Negeri Jakarta, 2013)
This study aims to determine significant differences in learning outcomes, in which the learning outcomes of students who are given the type of active learning quiz team is higher than conventional methods plus the subjects of class X Science Building Construction ArchitectureSMKN 1 Jakarta.Research site at SMKN 1 Jakarta. Research time in May-June 2013. The research method used was experimental method. The population in this study are all Class X Architecture Engineering Expertise Program SMKN 1 Jakarta 2012-2013 school year, amounting to 56 students, consisting of 26 students X TGB – 1 Class (Control Class) and 30 X TGB – 2 Class (Experiment Class) . Type in the research sample is saturated sampling where the number of samples used the same amount of population that is 56 students. Data collection techniques used were tests, totaling 30 items in the form of multiple choice. Testing the validity of the results obtained about 23 items were declared invalid. Reliability of the results obtained at 0.858 with very high levels of reliability.The average value of the experimental class is 81.87 higher than the average value of the control class is 75.54. The data comes from a normally distributed population and homogeneous. Hypothesis testing research conducted by t test with a significance level of 5% value obtained tobtained = 2.614, ttable = 1.675 then tobtained > ttable or 2.614 > 1.675, so reject H0 or hypothesis of the study accepted. The results are there differences in learning outcomes significantly Science Building where students are given learning outcomes of active learning quiz team type is higher than conventional methods plus. Based on the research results prove that the type of active learning quiz team can make students actively, increase motivation and attitude in the student's responsibility to learn and improve learning outcomes of students in the Science Building Construction SMK 1 Jakarta.